The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1974
DOI: 10.1126/science.183.4122.338
|View full text |Cite
|
Sign up to set email alerts
|

Near Identity of Cognitive Structure in Two Ethnic Groups

Abstract: As part of a large-scale family study in Hawaii, Americans of either Japanese or European ancestry were administered a battery of 15 cognitive tests. Principal component analyses (varimax rotations) yielded the same four major cognitive factors for each of the two ethnic groups, and these factors are defined by strikingly similar factor loadings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(38 citation statements)
references
References 4 publications
0
38
0
Order By: Relevance
“…In MISTRA, the Raven was presented via slides in a psychophysiology laboratory (Lykken, 1982), and administered on an untimed basis. DeFries et al (1974) reported internal consistency and retest reliabilities for the HB tests ranging from .58 for Immediate Visual Memory to .96 for Vocabulary.…”
Section: The Hawaii Battery Including Raven's Progressive Matrices (Hb)mentioning
confidence: 97%
“…In MISTRA, the Raven was presented via slides in a psychophysiology laboratory (Lykken, 1982), and administered on an untimed basis. DeFries et al (1974) reported internal consistency and retest reliabilities for the HB tests ranging from .58 for Immediate Visual Memory to .96 for Vocabulary.…”
Section: The Hawaii Battery Including Raven's Progressive Matrices (Hb)mentioning
confidence: 97%
“…In MISTRA, the Raven was presented via slides (Lykken, 1982), and administered on an untimed basis. DeFries et al (1974) reported retest and internal consistency reliabilities for the tests ranging from .58 for Immediate Visual Memory to .96 for Vocabulary.…”
Section: The Hawaii Battery Including Raven's Progressive Matrices (Hb)mentioning
confidence: 97%
“…The HB was developed to assess familial resemblance in cognitive ability in the Hawaii Family Study of Cognition (DeFries et al, 1974;Kuse, 1977). Two tests in this battery (Number Comparison and Social Perception) were not administered, again to avoid duplication of tasks.…”
Section: The Hawaii Battery Including Raven's Progressive Matrices (Hb)mentioning
confidence: 99%
“…In MISTRA, the Raven was presented via slides (Lykken, 1982), and administered on an untimed basis. DeFries et al (1974) reported internal consistency and retest reliabilities for the tests ranging from .58 for Immediate Visual Memory to .96 for Vocabulary.…”
Section: The Hawaii Battery Including Raven's Progressive Matrices (Hb)mentioning
confidence: 97%